The Kingfisher children's encyclopedia. - Kingfisher Publications (Boston : Kingfisher, 2004)
Presents more than 400 brief, alphabetically arranged entries on a variety of topics.
Includes index.
Keywords: Children's encyclopedias and dictionaries